Foreign exchange market interventions as monetary policy - Erik Post (Uppsala University, Department of Economics, 2006)
This paper sets up a simple model for interventions and interest rate setting assuming that the policy maker cares about deviations in inflation from a target level. Under a quadratic cost of interest rate adjustments and interventions the policy maker should use a combination of interest rate adjustment and interventions. According to the model interventions (purchases of foreign currency) will be negatively correlated with interest rate deviations from the steady state level but positively correlated with interest rate deviations pertaining to non-stabilizing motives or a binding zero lower bound. The model also predicts that interventions will be decreasing in inflation expectations and in the real exchange rate but increasing the expected interventions. Interventions are shown to be positively serially correlated if the policy maker cares about the future. Following the theoretical model closely two sets of regression results are presented using both Two Stage Least Squares and an Ordered Probit model. The empirical analysis uses daily intervention data for Australia, Japan and Sweden. Overall, the predictions of the model is supported in most dimensions indicating that interventions have been used in a way that is consistent with monetary policy considerations.
urn:nbn:se:uu:diva-83096
Keywords: E52; E58; F31; 330; foreign exchange interventions; monetary policy; central banks; Geldpolitik; Wechselkurspolitik; Zinspolitik; Australien; Japan; Schweden